THE LIFE HISTORY AND MICROHABITAT ECOLOGY OF A PHYTOTELM-BREEDING DAMSELFLY PERICNEMIS STICTICA IN JATIMULYO FOREST, YOGYAKARTA - Ainun Rubi Faradilla; Mariza Uthami; Bella Andini; Hening Triandika Rachman (BRIN Publishing (Penerbit BRIN), 2020)
This study aims to understand the life history and microhabitat ecology of a phytotelmata-breeding species, Pericnemis stictica. Data was collected at 46 breeding sites in the Jatimulyo Forest, Kulonprogo. Several parameters were recorded from each breeding site, i.e. plant species, diameters, depth, water depth, water volume, water pH, and water turbidity. Naiads and imagoes of P. stictica were measured morphometrically. The data taken was analyzed descriptively using Minitab 19. The results showed that 17 naiads of P. stictica were found in 13 bamboo stumps. The bamboo species most commonly used by P. stictica as a breeding site was Dendrocalamus asper. Naiads of P. stictica were found in the same habitat as mosquito larva from genera Toxorh-ynchites, Aedes, Armigeres, and Culex. During the rearing process, it was recorded that P. stictica naiads can eat more than ten mosquito larvae a day. Four males and one female imagoes of P. stictica were found. The imagoes were mostly found in a secondary forest with shady ravine areas. Imago's average total length was 7.19 cm. Naiad's final instar average size was 16.7 mm. Water depth, water temperature, bamboo depth, bamboo volume, and humidity were all positively correlated to P. stictica's phytotelmata-breeding behavior.